THE ROLE OF BLOCKCHAIN IN AUDITING: ENHANCING TRANSPARENCY AND REDUCING FRAUD RISKS - Yoosita Aulia; Nurul Huda; Zain Nizam (Journal Markcount Finance, 2026)
The rapid digitalization of financial and organizational processes has intensified concerns regarding audit transparency, data integrity, and fraud risk within conventional auditing systems. Traditional audit mechanisms often rely on ex post verification, fragmented records, and centralized control structures, which can limit real-time assurance and increase vulnerability to manipulation. This study aims to examine the role of blockchain technology in transforming auditing practices by enhancing transparency and reducing fraud risks. The research adopts a qualitative analytical approach based on an extensive review of peer-reviewed journal articles, professional auditing standards, and institutional reports published between 2016 and 2024. The findings indicate that blockchain-enabled auditing introduces immutable, time-stamped, and decentralized records that significantly improve audit trail reliability and real-time verification capabilities. Smart contracts and distributed ledgers reduce information asymmetry, limit opportunities for earnings manipulation, and strengthen internal control systems. Evidence also suggests that blockchain adoption reshapes the role of auditors from transaction verification toward continuous assurance and system oversight. The study concludes that blockchain technology has strong potential to enhance audit quality, transparency, and trust while mitigating fraud risks, although challenges related to scalability, regulatory alignment, data privacy, and auditor competency remain.